Policy Entrepreneurs, Legislators, and Agenda Setting: Information and Influence. Issue 3 (22nd March 2019) - Anderson, Sarah E.; DeLeo, Rob A.; Taylor, Kristin
Abstract : Policy entrepreneurs are thought to be instrumental in agenda change, yet we lack knowledge of how legislators perceive their role in the agenda formation process. Using data from a national survey of state legislators, we examine whether entrepreneurs shape the legislative agenda on disaster preparedness and relief, which types of entrepreneurs are most influential, and what strategies they use in their interactions with legislators. The results indicate that legislators who report contact with policy entrepreneurs are more likely to have introduced related legislation, evidence of the important link between entrepreneurs and policy change. While entrepreneurs utilize a variety of different strategies, the analysis reveals policymakers are particularly receptive to entrepreneurs who provide new and reliable information. This finding suggests the influence of entrepreneurs lies not only in their ability to define problems and build coalitions, but also in their distinctive ability to provide information to elected officials, an important role that has largely been overlooked by existing literature. Abstract : 我们认为政策企业家有助于改变政策议程，但是就立法者如何看待自己在议程形成过程中的作用来说，我们仍缺乏了解。本文通过从对州立法者的全国调查中得到的数据，研究了如下议题：企业家是否形成了备灾和救济的立法议程，哪些类型的企业家最具影响力，以及他们在与立法者的互动中使用了什么策略。结果表明，那些表示自己与政策企业家有一定联系的州立法者更有可能引入相关立法，这证明了政策企业家与政策变动之间的重要关联。虽然企业家能够使用各种不同的策略，但是本文的分析显示，政策制定者特别容易接受那些可以提供新的可靠信息的企业家。这一发现表明，企业家的影响不仅存在于他们定义问题和建立联盟的能力，还存在于他们是否拥有向民选官员提供信息的才能，而现有文献在很大程度上却忽视了这一重要作用。